KAJIAN MACAM JARAK TANAM SISTEM JAJAR LEGOWO DAN VARIETAS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza Sativa L.) - Istiqomah Istiqomah; Ana Amiroh; Dwi Choiriyah; Suharso Suharso (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2019)
Rice is a rice-producing food crop which now plays an important role in economic life in Indonesia. Namely rice as a staple food is very difficult to replace by other staples. Among them are corn, tubers, sago and other carbohydrate sources. So that the existence of rice is now a top priority for the community in meeting the needs of carbohydrate intake that can be filling and is a source of primary carbohydrates that are easily replaced into an energy source. Rice as a staple food is consumed by approximately 90% of the total population in Indonesia for daily essential food (Saragih,2001). How to plant with the jajar legowo system has the advantage that the plants are on the edge so that optimal sunshine can cause plant productivity to be high, facilitate weed control and pests / diseases, use of fertilizer more effectively and the availability of empty space for regulating water channel circulation on land (Sirrapa, 2011). This research was conducted using Factorial Randomized Block Design (RBD) method, which consisted of two factors and each factor consisting of 3 levels repeated 3 times, namely: J1: Conventional,J2: Jajar Legowo 2: 1,J3: Jajar Legowo 4: 1. Factor II: Varieties with 3 levels, V1: Situ Bagendit, V2: Ciherang,V3: IR-64. Of the two factors 9 combinations of treatments were obtained and repeated 3 times. Data obtained from observations were calculated by analysis of variance with the Fisher test (-F test at the level of 5% and 1%), if there were significant differences, it would be followed by the Smallest Significant Difference test (LSD 5%). The treatment of the legowo 4: 1 row system and the ciherang variety (V2J3) produces a better value than other treatments.